Synthesis of Metal Carborane Electrolytes for New Solid-state Battery Applications - Berger, Amanda Nicole (Curtin University, 2023)
The development of solid-state batteries as an alternative to Li-ion batteries for large-scale energy storage has become increasingly necessary as our society moves towards renewable energy sources. This PhD has focused on the synthesis and characterization of inorganic borate compounds as potential electrolytes for all-solid-state batteries, including the development of a new, cost-effective method to synthesise the closo- monocarbadodecaborate anion. This PhD also analysed the electrochemical potential of various mono- and divalent borate salts.